MICROBIAL PROCESSES OF CARBON TRANSFORMATION IN RHIZOSPHERE OF SUGAR BEET IN TYPICAL CHERNOZEM - Патика, М. В.; Москалевська, Ю. П. (Scientific Progress & Innovations, 2014)
The comparative analysis of the number by a functional targeting of the microbiota of sugar beet rhizosphere, which is involved in the transformation of carbon and its compounds, under different agrarian measures was conducted. The content of organic and labile water-soluble carbon in the chernozem typical and a condition of sugar beet crops is defined. It is established that localization of organic substances in the upper root-inhabited soil layer contributes to increase the number of microorganisms which involved in the carbon cycle in crop’s rhizosphere.